Sergeant pepper pots. - Turner, Alwyn W (New Statesman, 2012)
The article considers the Daleks, villainous robot-like characters in the science fiction television program "Doctor Who." The creation of the characters by writer Terry Nelson in 1963 and their origins in his memories of aerial bombing in World War II are discussed. The immediate popularity of the Daleks and their ongoing role in British popular culture is discussed. It is noted that the Daleks will return as characters for the 2012-2013 season of the program, its 50th anniversary.